Impact of the Metaverse Platform Mozilla Hubs on University Learner Satisfaction - Villa Munoz, Romulo Nayrod (Journal of Digital Contents Society, 2024)
This study examines the relationship between students’ experiences on the Metaverse platform Mozilla Hubs and their satisfaction with the platform as a learning tool. Data from 31 undergraduate students at an Ecuadorian university were analyzed using multiple regression and correlation analyses to assess the impact of user experience, learning outcomes, feature quality, and interaction effectiveness on overall satisfaction. Findings indicate that user experience and learning outcomes significantly influence satisfaction, with feature quality and interaction effectiveness also contributing strongly. These results underscore the importance of ease of navigation, high-quality features, and effective interactions in enhancing student satisfaction. This study offers valuable insights for educators and developers of virtual learning environments aiming to improve virtual learning experiences. KCI Citation Count: 0